(untitled) (Al-Qamar, 2022)
Education has been considered the cover value of human life and it creates awareness. Man’s relationship with religion and Allah Almighty has been established since eternity. Similarly, religion and education are also very closely related. From the Islamic point of view, human being has started his journey not with darkness and ignorance but with the light of knowledge. Islam made knowledge the first necessity. In the same way that Islam emphasizes on the acquisition of education, the concept of education exists in some form in other religions. Other religions have tried to create the impression that education is completely separate from religion, from this, it is known that apart from Islam, the concept of education is definitely found in other religions as well. It was found that education got importance in all religions but Islam has given more importance which any other religion did not given. Methodology of this research was Qualitative. In which we have referred to the original sources for Quranic verses and Hadith. The writing of the article is simple and eloquent. A list of sources and references is listed at the end of the paper.